MICROGRID PROTECTION DESIGN WITH OVERCURRENT RELAY GRADING ISSUE AT ISOLATED AREA IN INDONESIA - Levi Armariel, Benaya
Although the electrification ratio in Indonesia is already high, there are still many rural areas that do not have access to electricity, which called isolated areas. One of the ways to ensure electricity access in isolated areas is to use a microgrid, a micro-scale distribution network with the concept of electricity generation and distribution systems located in the same area as the load being served. In this final project research, the author will discuss the protection system on the isolated microgrid. The protection system aims to ensure the reliability of this distribution system in any situation and condition. The reliability will be proven by the system stability and coressponding with existing standard. First, the author will design a circuit that represents a distribution system. After that, the author designed a protection system focusing on the protection coordination between overcurrent relays and additional scheme if needed. The author will simulate 3phase short circuit fault and make variations in the location of the fault to test whether the circuit of the protection system that has been made is able to guarantee a reliable distribution system even when different locations of the 3phase short circuit fault occur. The author will do the same steps used before with the other system, which is Way Ngapu’s power system. The results obtained in this study are that the author was able to design a reliable protection system by designing the settings for each relay, coordinating between relays, and, if needed, carrying out additional schemes in the form of generator termination to ensure that each simulated fault can be isolated while guaranteeing the stability of the power system in each variation of the fault location.